Clock signal distribution with second order nodes: Design hints. (September 2021) - Piqueira, José Roberto C.; de Godoi, Antonio Carlos B.
Abstract: Despite being in use since the 1960's, clock distribution networks continue to be important, mainly since the digitalization of numerous electronic tasks, which demands precise time measures for synchronizing internal and external processes in computational and instrumentation applications. Designing clock distribution networks requires determination/estimation of the appropriate topologies and parameters that guarantee the mutual synchronization of the coupled oscillators. This problem has been largely studied in the telecommunications context, with digital hierarchies succeeding at providing precise multiplexing and switching, integrating services, and in the process, giving rise to a new era of communication. From a mathematical viewpoint, this work considers linear coupling factors, with the study of nonlinear effects still open. As the nodes of time distribution networks are phase-locked loops, considering nonlinearities is helpful for the design and operation of such systems. Herein, an overview of possible solutions concerning topologies and parameters is presented, allowing performance hints regarding network architectures and parameters to help designers. The main contribution is to put together and compare each solution while taking nonlinearities into account and to associate the application to be supported with the best clock distribution solution, thus providing simple rules of thumb for system design. Highlights: Acceptable one-way clock distribution networks are chain or star. Acceptable two-way clock distribution networks are chain or double-loop. In well controlled environments, one way topologies are better solutions. In noisy environments, two way topologies are better solutions.